Downsizing in plants—UV light induces pronounced morphological changes in the absence of stress. Issue 1 (7th June 2021) - Qian, Minjie; Rosenqvist, Eva; Prinsen, Els; Pescheck, Frauke; Flygare, Ann-Marie; Kalbina, Irina; Jansen, Marcel A.K.; Strid, Åke
Abstract: Ultraviolet (UV) light induces a stocky phenotype in many plant species. In this study, we investigate this effect with regard to specific UV wavebands (UV-A or UV-B) and the cause for this dwarfing. UV-A- or UV-B-enrichment of growth light both resulted in a smaller cucumber ( Cucumis sativus L.) phenotype, exhibiting decreased stem and petiole lengths and leaf area (LA). Effects were larger in plants grown in UV-B- than in UV-A-enriched light. In plants grown in UV-A-enriched light, decreases in stem and petiole lengths were similar independent of tissue age. In the presence of UV-B radiation, stems and petioles were progressively shorter the younger the tissue. Also, plants grown under UV-A-enriched light significantly reallocated photosynthates from shoot to root and also had thicker leaves with decreased specific LA. Our data therefore imply different morphological plant regulatory mechanisms under UV-A and UV-B radiation. There was no evidence of stress in the UV-exposed plants, neither in photosynthetic parameters, total chlorophyll content, or in accumulation of damaged DNA (cyclobutane pyrimidine dimers). The abscisic acid content of the plants also was consistent with non-stress conditions. Parameters such as total leaf antioxidant activity, leaf adaxial epidermal flavonol content and foliar total UV-absorbing pigment levels revealed successful UV acclimation of the plants. Thus, the UV-induced dwarfing, which displayed different phenotypes depending on UV wavelengths, occurred in healthy cucumber plants, implying a regulatory adjustment as part of the UV acclimation processes involving UV-A and/or UV-B photoreceptors. Abstract : A stocky phenotype develops in healthy cucumber plants as a regulatory adjustment toward UV-A and UV-B-enriched light, revealing a strong interaction between UV acclimation and developmental processes.